2015
DOI: 10.1128/aac.04348-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Intravenous Cidofovir for Life-Threatening Viral Infections in Pediatric Hematopoietic Stem Cell Transplant Recipients

Abstract: fChildren undergoing hematopoietic stem cell transplantation (HSCT) are at risk for life-threatening viral infections. Cidofovir is often used as a first-line agent for adenovirus infections, despite the absence of randomized controlled trials with HSCT patients, and as a second-line agent for resistant herpesvirus infections. The frequency and severity of adverse effects, particularly nephrotoxicity, in pediatric HSCT recipients are unclear, and pharmacokinetics (PK) of cidofovir in children have not previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 25 publications
(40 reference statements)
0
26
0
4
Order By: Relevance
“…Despite administration of cidofovir, 43% to 50% of allogeneic HCT recipients with ADV viremia die: early administration of cidofovir reportedly improves the prognosis of ADV infections. [ 18 , 19 ] Although our patient had not received allogeneic HCT and T-cell-specific immune suppressants, uncontrolled underlying ALL, concurrent fungal pneumonia, and delayed cidofovir administration could have led to the grave outcome. Fatal ADV infections in allogeneic HCT recipients with concurrent bacterial and fungal coinfections have been reported, although the ADV DNA titers from blood samples were low.…”
Section: Discussionmentioning
confidence: 99%
“…Despite administration of cidofovir, 43% to 50% of allogeneic HCT recipients with ADV viremia die: early administration of cidofovir reportedly improves the prognosis of ADV infections. [ 18 , 19 ] Although our patient had not received allogeneic HCT and T-cell-specific immune suppressants, uncontrolled underlying ALL, concurrent fungal pneumonia, and delayed cidofovir administration could have led to the grave outcome. Fatal ADV infections in allogeneic HCT recipients with concurrent bacterial and fungal coinfections have been reported, although the ADV DNA titers from blood samples were low.…”
Section: Discussionmentioning
confidence: 99%
“…ADV, and several other viruses are also treated with cidofovir, which in those cases might be better tolerated than in CMV infections. 91 Alternatively, treatment with a modified dosing regimen of cidofovir was well tolerated and high-risk ADV infections resolved in seven pediatric allogeneic hematopoietic progenitor cell transplant recipients. 92 …”
Section: Limits Of Established Methods For Treatment Of Viral Infectimentioning
confidence: 99%
“…Cidofovir has been shown to effectively manage adenoviral infections in several studies. An open label, nonrandomized, single pilot study concluded that cidofovir could be safely used in paediatric hematopoietic stem cell transplant recipients 6 . Cidofovir is a nucleoside analog that prevents DNA polymerization and DNA replication of viruses.…”
Section: What Is Known and Objectivementioning
confidence: 99%